Research, design, and simulation of automatic spot welding system for kia k3000s truck bed - Phung, Trí Công; Nguyen , Duy Anh (Journal of Technical Education Science, 2015)
This paper addresses an automatic assembly system for the lateral part of Kia K3000S truck bed. This assembly procedure is still done manually by workers in Thaco company. In this paper, the authors suggest an automation solution from assembling metal bars to grasping inox plate and finally welding the inox plate into metal bars. Besides designing mechanical parts, electric circuits are also considered so that the system can work accurately and stably. The idea is verified by professional simulation software for industrial robots.